PENGEMBANGAN BAHAN AJAR E-BOOK PRAKTIKUM AKUNTANSI LEMBAGA/INSTANSI PEMERINTAHAN BERBASIS ANDROID DENGAN PENDEKATAN PROBLEM BASED LEARNING SEBAGAI SUMBER BELAJAR ALTERNATIF - Multiana, Ayun; Bahtiar, Moh. Danang (STKIP PGRI Situbondo, 2025)
The achievement of learning objectives is supported by using appropriate teaching materials. E-books, a type of digital teaching material that utilizes technology in the field of education, can be used as an alternative to improve learning outcomes. This study aims to create an android-based teaching material product using a problem-based learning approach (Problem-Based Learning) for accounting practicum material for government institutions or agencies, analyze whether teaching materials are feasible to use, and analyze how students respond to the teaching materials developed. The type of research used is the R&D (Research and Development) model with the 4D model developed by Thiagarajan, Semmel, and Semmel. This model consists of four stages: defining, designing, developing, and disseminating.